INFLUENCE OF CIRCADIAN RHYTHMS ON LUNG FUNCTIONS AND SLEEP WAKE CYCLE - A, SABARITHA.; G, .SRIDEVI. (International Journal of Psychosocial Rehabilitation, 2025)
Body is a biological clock where the cyclic process that occurs within every twenty-four hours is called circadian rhythm. Circadian rhythms are autonomous. Circadian rhythm helps to diagnose the onset and severity of the disease. Circadian rhythms are lost due to systemic inflammation. These rhythms are created and maintained by interactive positive and negative transcriptional and translational feedback loops. The understanding of how peripheral clocks drive physiology is relatively poor. Hence this study is done to identify when blocks occur during peak flow of circadian rhythms and to reduce the inflammation. The aim of this study is to determine the influence of circadian rhythms on lungs function and sleep cycle of normal healthy subjects the study is based on cross sectional analysis. A survey was conducted among random populations to study the influence of circadian rhythm on lung functions and sleep wake cycle using a questionnaire named morningness and eveningness scale. The questionnaire was distributed through an online survey link (i.e) google forms. Nearly 150 members participated in it. The results were collected and statistically analysed through spss software, version 22 and frequency and percentage analysis was used to present the data. Statistical analysis used was chi square test and the significance value was fixed at p